ADVENTURE BASED COUNSELING DALAM LAYANAN BIMBINGAN DAN KONSELING KELOMPOK - Agung Nugraha (Journal of Innovative Counseling : Theory, Practice, and Research, 2018)
This paper aims to analyze Adventure Based Counseling (ABC) with a focus on the study of ABC application in group counseling and guidance services. Intensive literature review of the nature of ABC, the underlying theory of ABC, the positive implications of ABC in group counseling and guidance services in facilitating the counselee's personal development is the research methodology of this paper. Therefore, this paper is expected to contribute to the development of knowledge in the field of group counseling and guidance services.